2010
DOI: 10.1038/jhg.2010.163
|View full text |Cite
|
Sign up to set email alerts
|

A Japanese case of ichthyosis follicularis with atrichia and photophobia syndrome with an MBTPS2 mutation

Abstract: Ichthyosis follicularis with atrichia and photophobia (IFAP) syndrome is a rare genetic disorder characterized by the triad of ichthyosis follicularis, alopecia and photophobia. Previous studies have identified five missense mutations in the membranebound transcription factor protease, site 2 (MBTPS2) gene in European patients with this syndrome. In this study, we detected the 1286G4A (Arg429His) mutation in MBTPS2 in a Japanese patient with IFAP syndrome. This mutation has previously been detected in a German… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Recently a patient with the p.I258.M mutation was described with mild B cell lymphopenia and poor antibody response [6]. Other authors have reported atopic features like urticaria, atopic dermatitis, cow's milk protein allergy and anaphylaxis [3,4,11,16]. The presence of hypogammaglobulinemia in our patient might suggest a primary B lymphocyte disfunction in IFAP/BRESHECK syndrome playing a role in the pathogenesis of recurrent skin and respiratory tract infections.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Recently a patient with the p.I258.M mutation was described with mild B cell lymphopenia and poor antibody response [6]. Other authors have reported atopic features like urticaria, atopic dermatitis, cow's milk protein allergy and anaphylaxis [3,4,11,16]. The presence of hypogammaglobulinemia in our patient might suggest a primary B lymphocyte disfunction in IFAP/BRESHECK syndrome playing a role in the pathogenesis of recurrent skin and respiratory tract infections.…”
Section: Discussionmentioning
confidence: 70%
“…The first reported patients were two male brothers of a German family with IFAP syndrome, who both died in the first 2 years after birth [3]. The third report was a 5 years-old Japanese male patient with IFAP syndrome [4]. The fourth report was a 4 years-old Japanese male patient with BRESHECK syndrome [7].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recurrent infections are often noted in IFAP syndrome. External genitalia are almost always normal; few cases presented with cryptorchidism [3,14,16,17], and one with a hypospadias [17]. Dental development is normal.…”
Section: Clinical Descriptionmentioning
confidence: 99%
“…Nevertheless, no clear phenotype/genotype correlation could be evidenced. Indeed, recently a Japanese patient with IFAP syndrome carrying the c.1286G > A (p.Arg429His) mutation in MBTPS2, was not as severely affected as the patients from a German family carrying the same mutation [16,17]. Furthermore, it was shown that the p.Asn508Ser mutation causes IFAP syndrome and a close allelic syndrome named "Keratosis follicularis spinulosa decalvans" [17,27].…”
Section: Etiologymentioning
confidence: 99%